Regulatory dendritic cell infusion prolongs kidney allograft survival in non-human primates - Ezzelarab, M. (2013)
We examined the influence of regulatory dendritic cells (DCreg), generated from cytokine-mobilized donor blood monocytes in vitamin D3 and IL-10, on renal allograft survival in a clinically-relevant rhesus macaque model. DCreg expressed low MHC class II and costimulatory molecules, but comparatively high levels of programmed death ligand-1 (B7-H1), and were resistant to pro-inflammatory cytokine-induced maturation. They were infused intravenously (3.5–10×10(6)/kg), together with the B7-CD28 costimulation blocking agent CTLA4Ig, 7 days before renal transplantation. CTLA4Ig was given for up to 8 weeks and rapamycin, started on day −2, was maintained with tapering of blood levels until full withdrawal at 6 months. Median graft survival time was 39.5 days in control monkeys (no DC infusion; n=6) and 113.5 days (p< 0.05) in DCreg-treated animals (n=6). No adverse events were associated with DCreg infusion, and there was no evidence of induction of host sensitization based on circulating donor-specific alloantibody levels. Immunologic monitoring also revealed regulation of donor-reactive memory CD95(+) T cells and reduced memory/regulatory T cell ratios in DCreg-treated monkeys compared with controls. Termination allograft histology showed moderate combined T cell- and Ab-mediated rejection in both groups. These findings justify further pre-clinical evaluation of DCreg therapy and their therapeutic potential in organ transplantation.